Energy, exergy and economic analysis of industrial boilers - Saidur, Rahman; Ahamed, Jamal Uddin; Masjuki, Haji Hassan (Elsevier, 2010)
In this paper, the useful concept of energy and exergy utilization is analyzed, and applied to the boiler system. Energy and exergy flows in a boiler have been shown in this paper. The energy and exergy efficiencies have been determined as well. In a boiler, the energy and exergy efficiencies are found to be 72.46 and 24.89, respectively. A boiler energy and exergy efficiencies are compared with others work as well. It has been found that the combustion chamber is the major contributor for exergy destruction followed by heat exchanger of a boiler system. Furthermore, several energy saving measures such as use of variable speed drive in boiler's fan energy savings and heat recovery from flue gas are applied in reducing a boiler energy use. It has been found that the payback period is about 1 yr for heat recovery from a boiler flue gas. The payback period for using VSD with 19 kW motor found to be economically viable for energy savings in a boiler fan.